PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SMP - Situmorang, Nova Lenta; Siregar, Nurhasanah (Universitas Islam Sumatera Utara, 2024)
This research aims to improve students' ability to understand mathematical concepts at SMP Negeri 21 Medan by applying the Discovery Learning learning model. This research is classroom action research carried out in two cycles. The subjects of this research were students of VIII-5 SMP Negeri 21 Medan with a total of 31 students. Each cycle consists of 4 stages, namely planning, implementation, observation/evaluation and reflection. The results of the research show that students' ability to understand mathematical concepts can increase after implementing the discovery learning model. The increase was obtained through the average student score from 57.52 in the poor category, increasing in the first cycle to 68.11 in the poor category and increasing in the second cycle to 77.81 in the sufficient category. Improvement was also obtained from students' classical abilities, where in the first cycle 16 students (51.61%) completed it. Then, in cycle II, it was found that 27 students (87.1%) had completed classically. So it is concluded that the application of the Discovery Learning learning model can improve the ability to understand mathematical concepts of students in class VIII SMP Negeri 21 Medan.